Tumor MMP-1 Activates Endothelial PAR1 to Facilitate Vascular Intravasation and Metastatic Dissemination - Juncker-Jensen, Anna (2013)
Intravasation, the active entry of primary tumor cells into the vasculature, remains the least studied step in the metastatic cascade. Protease-mediated escape and stromal invasion of tumor cells represent widely-accepted processes leading up to the intravasation step. However, molecular factors that contribute directly to tumor cell vascular penetration have not been identified. In this study, the in vivo role of the collagenolytic protease, MMP-1, in cancer cell intravasation and metastasis was analyzed by employing a highly-disseminating variant of human HEp3 epidermoid carcinoma, HEp3-hi/diss. Whereas naturally-acquired or experimentally-induced MMP-1 deficiency substantially suppressed HEp3-hi/diss intravasation, supplementation of recombinant MMP-1 to MMP-1-silenced primary tumors, restored their impaired vascular dissemination. Surprisingly, abrogation of MMP-1 production and activity did not affect significantly HEp3-hi/diss migration or matrix invasion, suggesting non-collagenolytic mechanisms underlying MMP-1-dependent cell intravasation. In support of such non-collagenolytic mechanisms, MMP-1 silencing in HEp3-hi/diss cells modulated the microarchitecture and integrity of the angiogenic vasculature in a novel microtumor model. Concomitantly, MMP-1 deficiency led to decreased levels of intratumoral vascular permeability, tumor cell intravasation and metastatic dissemination. Taking advantage of PAR1 deficiency of HEp3-hi/diss cells, we further demonstrate that endothelial PAR1 is a putative non-tumor-cell/non-matrix target, activation of which by carcinoma-produced MMP-1 regulates endothelial permeability and transendothelial migration. The inhibitory effects of specific PAR1 antagonists in live animals have also indicated that the mechanisms of MMP-1-dependent vascular permeability in tumors involve endothelial PAR1 activation. Together, our findings mechanistically underscore the contribution of a tumor MMP-1/endothelial PAR1 axis to actual intravasation events manifested by aggressive carcinoma cells.